Nutraceuticals and human blood platelet function : applications in cardiovascular health - Duttaroy, Asim K. (John Wiley & Sons Ltd, 2018)
"A comprehensive review of the impact of dietary nutraceuticals on platelet function and its relationship to cardiovascular disease"--Provided by publisher.